PERBANDINGAN STRATEGI PEMERINTAH DAERAH DALAM PENGELOLAAN PARIWISATA HALAL DI KOTA BANDA ACEH DAN KOTA SABANG - Humairah Fatin Sausan; Dedy Sanjaya; M. Afi Algifari; Nurul Kamaly; Khalid Vikriadi (LPPM Universitas Muhammadiyah Gorontalo, 2026)
Sabang through a qualitative approach based on literature studies. By reviewing various regulations, official documents, and scientific literature, this study found that the two regions implement significantly different governance models. Banda Aceh places more emphasis on an institutional approach that emphasizes strengthening regulations, formalizing halal branding, and legitimizing policies structurally. In constrast, Sabang City adopts a more adaptive, destination-based approach by organically integrating halal values into the marine and mature tourism sectors. These differences in strategy demonstrate that regional characteristics, institutional capacity, and local development orientation significantly determine the direction of tourism policy. Therefore, this study concludes that halal tourism development cannot be achieved with a uniform approach but must be addressed basd on the specific potential and conditions of the region. These findings contribute to the region’s contribution to strengthening the halal tourism ecosystem in Aceh